Modeling Risk Perception Through Investment Attributes: A ‎CHAID-Based Analysis - Khatri, Dr. Namrata N.; Ramchandani, Dr. Vinita; Maurya, Dr. Ruchi; Desai, Dr. Jaydipsinh R. (International Journal of Accounting and Economics Studies, 2025)
Individuals seek higher returns with minimum risk. Risk-taking ability is influenced by various factors, including demographics, upbringing, and culture; however, many behavioral factors are challenging to understand and quantify. In contrast, observable characteristics ‎such as the mode of investment are comparatively easier to capture, and individuals can respond ‎to such questions more accurately. The present study aims to link these observable characteristics, namely annual family investment, major earning source, preferred investment period, investment frequency, years of investment experience, and mode of investment, with ‎the risk-taking ability of individual investors using the CHAID (Chi-square automatic interaction detection) tool.
Keywords: Risk-Taking Ability; Risk Perception; Investor Profile; Investment Attributes; Behavioral ‎Finance; CHAID Decision Tree